2011
DOI: 10.1093/biolreprod/85.s1.125
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Deletion of Wnt7a Inhibits Uterine Gland Morphogenesis and Compromises Adult Fertility in Mice.

Abstract: The success of postnatal uterine morphogenesis dictates, in part, the embryotrophic potential and functional capacity of the adult uterus. The definitive role of Wnt7a in postnatal uterine development and adult function requires a conditional knockout, because global deletion disrupts mü llerian duct patterning, specification, and cell fate in the fetus. The Wnt7a-null uterus appears to be posteriorized because of developmental defects in the embryo, as evidenced by the stratified luminal epithelium that is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 45 publications
(76 reference statements)
4
55
0
3
Order By: Relevance
“…Those uteri contained unimplanted blastocysts in which the trophectoderm was in clear apposition to an intact LE with no evidence of stromal cell decidualization. Similarly, mice lacking uterine glands do not express Lif and exhibit a defect in blastocyst implantation (12,(33)(34)(35)(36)(37)(38). Thus, uterine glands and, by inference, their secretions do not influence preimplantation embryo growth and development but are required for implantation and successful establishment and maintenance of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those uteri contained unimplanted blastocysts in which the trophectoderm was in clear apposition to an intact LE with no evidence of stromal cell decidualization. Similarly, mice lacking uterine glands do not express Lif and exhibit a defect in blastocyst implantation (12,(33)(34)(35)(36)(37)(38). Thus, uterine glands and, by inference, their secretions do not influence preimplantation embryo growth and development but are required for implantation and successful establishment and maintenance of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Lif-null and uterine-glandless mice (Pgr Cre mice with conditional deletion of Foxa2, Ctnbb1, Lef1, Wnt4, Wnt5a, or Wnt7a and also mice with progesterone-induced uterine gland knockout, PUGKO) all exhibit deficiencies in peri-implantation Lif expression and defects in blastocyst implantation (12,(33)(34)(35)(36)(37). Of note, blastocysts from UGKO mice are implantation competent when transferred into normal uteri (38).…”
Section: On Gd 35 Induces the Expression Of Lif In The Glands Of Thementioning
confidence: 99%
“…In a study, conditional activation of β-catenin caused an increased amount of enlarged glands in the uterus, whereas upon ablation of β-catenin, the endometrium contained no glands [47]. β-catenin protein was present predominantly in the uterine epithelia and was not different between control and mutant uteri with Wnt7a depletion during postnatal development of mice [40].…”
Section: Wnt Signaling In Uterine Receptivitymentioning
confidence: 96%
“…It was found that, postnatal ablation of Wnt7a after birth in the mouse uterus caused infertility depending on disruption of endometrial gland morphogenesis. Although uterus histology was not affected by an experimental model of Wnt7a conditional null allele, mutant uteri lacked endometrial glands and as a result, implantation did not occur in the uteri of mutant mice [40]. Wnt4 was also shown to be associated with development of endometrial glands in mice [41].…”
Section: Wnt Signaling In Uterine Receptivitymentioning
confidence: 98%
See 1 more Smart Citation